Partisipasi Yayasan Emas Indonesia dalam Program Pembentukan Karakter Anak Jalanan di Kota Semarang, Jawa Tengah - Mia Jessica Lorena Tarigan; Titik Djumiarti; Teuku Afrizal (Journal of Public Policy and Management Review, 2022)
Participation is the participation of a person into an organization and is managed properly. This study examines the participation of the Yayasan Emas Indonesia Foundation in the character forming program for street children in the city of Semarang. This study aims to analyze the participation of the Indonesian Gold Foundation in the character building program for street children in the city of Semarang. This study used descriptive qualitative method. Sources of data in this study obtained from interviews, observations, and documentation. The informant selection technique was carried out using purposive sampling and accidental sampling. This study uses the theory of participation success dimensions. The results obtained, namely indicators of trust, responsibility and concern have been fulfilled and support the implementation of participation. Indicators that do not support the participation carried out are contributions, quality and quantity, as well as ideas or aspirations. The contribution is still lacking because the aspects in the contribution have not been fulfilled. Quality and quantity have not yet been implemented. The indicators for ideas or aspirations have not gone well due to limited funds. The driving factor for the participation of the Indonesian Gold Foundation is the opportunity, the willingness and the ability. The inhibiting factors for participation are limited human resources and inadequate materials or facilities in the ongoing participation. The advice that can be given is that the Indonesian Gold Foundation can improve the management of existing resources and participate in many events with various parties to introduce the Indonesian Gold Foundation to the public.